Evolution of fetal lung stiffness during gestation in two different congenital malformations. Issue 4 (10th March 2019) - Mottet, Nicolas; Metz, Jean‐Patrick; Chaussy, Yann
Abstract: This report is aimed at opening a new reflexion about exploration of fetal lungs malformations with 2‐D ultrasound shear wave elastography (2D‐SWE) in two fetuses. These preliminary results are drawn from the ELASTOMAP study, which was designed to explore feasibility of 2D‐SWE on fetal lungs. Fetus A presented Congenital Pulmonary Airway Malformation and fetus B congenital obstructive emphysema. We estimated every 3 weeks the Congenital Pulmonary Airway Malformation Volume Ratio (CVR) of the malformation and we evaluated stiffness by 2D‐SWE. Stiffness of the lesion and the normal lung were compared to liver stiffness using Lung to Liver Elastography (LLE) ratio. Interestingly, CVR and LLE ratios evolved differently in these two lesions caused by distinct physiopathological processes. In both cases, LLE ratio' variations preceded that of CVR. LLE ratio of the normal lung was constant through gestation. 2D‐SWE could be a promising tool to describe stiffness evolution in fetal lungs malformations.